(untitled) (International Journal of Engineering and Computer Science, 2018)
In this study, speed/position control of real time static magnetic Direct Current (DC) motor which can communicate with wireless using Matlab platform and PIC microcontroller was carried out. The study consists of three sections: developing DC motor speed/position unit, developing wireless communication module, and developing Matlab-Gui user interface. In the study, PIC16F876A was used as microcontroller, 2x16 character LCD screen was used as real time user interface, HC-05 Bluetooth adaptor was used for Bluetooth communication, and Matlab-Gui program was used as computer interface. An application card was designed for the user to carry out speed and position control of a DC motor which is in real environment and it was achieved. As a result of the experiments conducted, it was seen that the study is capable of measuring required rotation data with an error less than 1%. Data of position is again obtained from optical encoder. Wireless communication is securely provided and there occurred no data loss. Speed/position control of the wireless DC motor with high resolution and security was achieved with this study